Flavor Roasted Chicken Salted Egg Agroindustry In Lampung Province - Dea Ayu Larasati (LPPM Universitas PGRI Sumatera Barat, 2024)
The aim of this research is to analyze the feasibility and strategy for developing the salted egg agro-industry for purebred chickens in Lampung Province. Type of quantitative descriptive research. Data collection will be carried out in May - July 2023. The research location for the feasibility analysis and development strategy for agro-industry based on purebred chicken salted eggs will be carried out in Lampung Province. The research method used is a survey method and interviews with experts related to determining the feasibility analysis and strategy for developing agro-industry based on purebred chicken salted eggs. Determining the location of the salted egg agro-industry for purebred chickens in Lampung Province will use the Exponential Comparison Method (MPE). Development strategy with internal, external factor analysis and SWOT analysis. Determining criteria for selecting agro-industrial locations through brainstorming (exchanging opinions) with experts and literature study, then analyzed using the Exponential Comparison Method (MPE). Based on analysis of market and marketing, technical and technological, and financial aspects of the salted egg agro-industry, purebred chickens meet the business feasibility criteria, namely a positive NPV of IDR 77,301,102, Payback Period 3 years 1 month, IRR greater than the 6% discount factor, namely 32.76 % and the B/C ratio value is greater than 1, namely 1.08. The strategy used to develop the salted egg agro-industry for purebred chickens is an aggressive strategy, namely by utilizing all strengths to seize and exploit opportunities as much as possible. Further research is needed regarding the most potential market segmentation.